Effective discrimination of gas-phase peptide conformers using TIMS-ECD-ToF MS/MS. Issue 43 (26th October 2021) - Jeanne Dit Fouque, K.; Wellmann, M.; Leyva Bombuse, D.; Santos-Fernandez, M.; Cintron-Diaz, Y. L.; Gomez-Hernandez, M. E.; Kaplan, D.; Voinov, V. G.; Fernandez-Lima, F.
Abstract : Model peptides ( e.g., substance P, bradykinin, angiotensin I and AT-Hook 3) were studied using ion mobility and ECD/CID fragmentation in a TIMS-q-EMS-ToF MS/MS platform. Abstract : In the present work, four, well-studied, model peptides ( e.g., substance P, bradykinin, angiotensin I and AT-Hook 3) were used to correlate structural information provided by ion mobility and ECD/CID fragmentation in a TIMS-q-EMS-ToF MS/MS platform, incorporporating an electromagnetostatic cell (EMS). The structural heterogeneity of the model peptides was observed by (i) multi-component ion mobility profiles (high ion mobility resolving power, R ∼115–145), and (ii) fast online characteristic ECD fragmentation patterns per ion mobility band (∼0.2 min). Particularly, it was demonstrated that all investigated species were probably conformers, involving cis / trans -isomerizations at X-Pro peptide bond, following the same protonation schemes, in good agreement with previous ion mobility and single point mutation experiments. The comparison between ion mobility selected ECD spectra and traditional FT-ICR ECD MS/MS spectra showed comparable ECD fragmentation efficiencies but differences in the ratio of radical (˙)/prime (′) fragment species (H˙ transfer), which were associated with the differences in detection time after the electron capture event. The analysis of model peptides using online TIMS-q-EMSToF MS/MS provided complementary structural information on the intramolecular interactions that stabilize the different gas-phase conformations to those obtained by ion mobility or ECD alone.